Productive quality of Awassi rams in Rajasthan - DANG, A K; JOSHI, A; NAQVI, S M K; MITTAL, J P (The Indian Journal of Animal Sciences, 2013)
Superior productive performance of Awassi breed of sheep is likely to improve production of nondescript sheep in arid and semi-arid regions of India. An experiment was conducted to study reproductive adaptability of Awassi rams under semi-arid climate of Rajasthan. The sexual behaviour, libido and semen quality of 2 adult Awassi rams kept on semi-intensive management system were studied. The sexual behaviour studied in terms of sniffing/nosing of external genitalia, kicking with forelegs, moving in and out ofthe tongue, courting grunts was similar to rams of native breeds, and Awassi were able to donate good quality semen sufficient for one oestrous cycle and each of these ram was capable of ejaculating 3-4 times during the span of 15 min. The semen volume, sperm motility and sperm concentration, in first and in subsequent ejaculations were similar to native and Awassi rams. It was apparent from these results that A wassi rams are well adapted, in their sexual behaviour, libido and semen characteristics under semi-arid region of Rajasthan.